2012
DOI: 10.2164/jandrol.110.012278
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VASA mRNA in Testis as a Significant Predictor of Sperm Recovery by Microdissection Testicular Sperm Extraction in Patient With Nonobstructive Azoospermia

Abstract: It would be of value to evaluate whether expression levels of mRNAs playing important roles in spermatogenesis could be used as predictors of successful testicular sperm recovery by microdissection testicular sperm extraction (TESE) in patients with nonobstructive azoospermia (NOA). This study included 52 patients with NOA who underwent therapeutic sperm retrieval by micro-TESE at our institution. We measured expression levels of VASA, outer dense fiber-1 (ODF1), ODF2, and sperm mitochondria-associated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…Similar results were obtained with the BOULE mRNA occurrence [24]. Ando et al showed that expression of VASA , ODF1 , ODF2 (outer dense fiber 1 and 2) and SMCP (sperm mitochondria-associated cysteine-rich protein) genes was significantly stronger in the successful TESE group [25]. Other genes expressed in post-meiotic stage may also be good candidates for the prediction of successful fertilization.…”
Section: Discussionsupporting
confidence: 74%
“…Similar results were obtained with the BOULE mRNA occurrence [24]. Ando et al showed that expression of VASA , ODF1 , ODF2 (outer dense fiber 1 and 2) and SMCP (sperm mitochondria-associated cysteine-rich protein) genes was significantly stronger in the successful TESE group [25]. Other genes expressed in post-meiotic stage may also be good candidates for the prediction of successful fertilization.…”
Section: Discussionsupporting
confidence: 74%
“…The phenotype of MA and male sterility in cattle-yak hybrids [13] is consistent with the phenotype of Mvh gene knockout mice [10], suggesting that the mRNA levels of Bvh in the testicular tissue may be associated with the male sterility of cattle-yak hybrids. Ando et al [43] found that transcription levels of Vasa in testicular tissue of successful testicular sperm extraction (TESE) patients with nonobstructive azoospermia (NOA) were higher than that of unsuccessful TESE groups, and suggested that measuring Vasa mRNA in testis could be a useful adjunct to conventional parameters for predicting sperm retrieval by micro-TESE in patients with NOA. The Vasa mRNA and protein levels were significantly decreased in patients with oligozoospermia: their mRNA level was only 1/5 of the normozoospermic men [44].…”
Section: Discussionmentioning
confidence: 99%
“…Some seminiferous tubules near OFSCs showed mature spermatogenesis ( Figure 5D,E, white arrow), and some did not ( Figure 5D,E, black arrow). Antibodies against human/rat P450, Sox-9, and VASA were used to identify Leydig cells [27], Sertoli cells [28], and sperm [29], respectively. In all 10 testis sections stained with P450, some hB2M-expressing cells differentiated into P450-expressing cells could be observed in each tissue section ( Figure 5E).…”
Section: Local Injection Of Orbital Fat-derived Stem Cells Supports Lmentioning
confidence: 99%